Mechanisms for Increasing the Convenience of Service for Passengers and Economic Efficiency through Optimizing the Tariff Policy in Public Transport (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
Public transport is the most widely used type of transport by the population, which is considered the most widely used type of transport by the population due to its low cost, speed and convenient payment system, as well as reducing traffic congestion on the moving road.